Smallholder rubber sector in the Moneragala district: Potentials and constraints - Dissanayake D M A; Edirisinghe J C; Wijesuriya Wasana (Bulletin of the Rubber Research Institute of Sri Lanka, 2005)
As a timely and appropriate initiative to increase the national rubber production, the Government has taken steps to expand the rubber cultivation into the intermediate agro-climatic zones of Sri Lanka. These non-traditional areas have great potential for profitable rubber cultivation. Yet, there are constraints for rubber cultivation, which can affect the profitability. This article attempts to highlight these potentials and constraints in the smallholder rubber sector in the Moneragala area in the low country intermediate zone of Sri Lanka
Keywords: Rubber sector